IMF Staff papers : Volume 23 No. 2. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1976)
This paper provides the nexus between short-term interest rates, private monetary capital flows, and the exchange rate under managed floating. It questions the belief held by many economists that capital flows necessarily have benign effects that prevent large erratic movements in the exchange rate from taking place. The approach employed in the study is to specify a model of the balance of payments of the Federal Republic of Germany including the demand for and the supply of base money as well as policy reaction functions explaining the central bank net demand for domestic assets (monetary policy) and foreign assets (intervention policy). The major finding of the study is that the experience of the Federal Republic of Germany with floating does not bear out the faith that many economists have had in the stabilizing role of short-term capital flows. Relatively small variations in the interest rate differential between Frankfurt and the Euro-dollar market have led to large fluctuations in the exchange rate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet